Tuning adsorption properties of GaxIn2−xO3 catalysts for enhancement of methanol synthesis activity from CO2 hydrogenation at high reaction temperature - Akkharaphatthawon, Naphattanun; Chanlek, Narong; Cheng, C. K.; Chareonpanich, Metta; Limtrakul, Jumras; Witoon, Thongthai (Elsevier, 2019)
Light olefins can be produced from CO2 hydrogenation in a single reactor using a combination of a methanol synthesis catalyst and a methanol-to-olefin (MTO) catalyst. However, commercial methanol synthesis catalysts are active at low temperatures (200–260 °C), while MTO reaction is feasible at higher temperatures (>300 °C). Herein, we report the CO2 hydrogenation to methanol at high temperatures (320–400 °C) over GaxIn2−xO3 catalysts. By tuning the Ga/In ratios, phase, crystallinity, pore structure, morphology, electronic properties as well as adsorptive properties of GaxIn2−xO3 catalysts can be modified. At the lowest temperature (320 °C), the pure In2O3 shows the highest methanol yield. However, the maximum methanol yield declines significantly with increasing reaction temperatures. Incorporation of Ga into the In2O3 crystal lattices at x = 0.4 (Ga0.4In1.6O3) maximizes the methanol yield at higher reaction temperatures of 340–360 °C. This enhancement can be attributed to an increased binding energy of adsorptive molecules with the catalyst surface to promote the hydrogenation of CO2 to methanol. Further increasing Ga content (x > 0.4) leads to greatly strengthen the binding for adsorptive molecules, resulting in a lower methanol yield and the formation of methane. The surface chemisorbed oxygen is found to be a key factor determining the CO yield.